2012
DOI: 10.2308/ajpt-50328
|View full text |Cite
|
Sign up to set email alerts
|

The Auditor's Approach to Subsequent Events: Insights from the Academic Literature

Abstract: SUMMARY Approximately one-third of the PCAOB's inspection reports and several SEC enforcement releases identify deficiencies in the audit of subsequent events (SEs). Despite these issues, little research has been conducted to understand how and why these deficiencies occur. This paper integrates the psychology and behavioral accounting literatures to develop a model of the factors that influence the effectiveness of SE audit procedures. The model suggests that the effectiveness of these procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 167 publications
1
28
0
1
Order By: Relevance
“…From the above we can conclude that auditors comply with the requirements of the ISA 560 for subsequent events that occur between the balance sheet date and the date of the auditor's report, this result agree with the results of the study of Chung et al, (2013)and Carmichael (2004) or the results of PCAOB. Also we can conclude that auditors don't comply with the requirements of this standard for these events that occur after the auditing report date.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…From the above we can conclude that auditors comply with the requirements of the ISA 560 for subsequent events that occur between the balance sheet date and the date of the auditor's report, this result agree with the results of the study of Chung et al, (2013)and Carmichael (2004) or the results of PCAOB. Also we can conclude that auditors don't comply with the requirements of this standard for these events that occur after the auditing report date.…”
Section: Resultssupporting
confidence: 82%
“…This model provides a theoretical basis that can be relied upon in future studies which will deal with the reasons for the gaps and deficits and suggested possible strategies that can be used by auditors to improve the effectiveness of auditing subsequent events. Researchers found that a third of the checking process that have been done in PCAOB and releases issued by the SEC identify gaps in auditing of the previous events (Chung et al, 2013, Carmichael 2004. SEC report has recently requested reducing the period between the balance sheet date and the final financial report date to reduce subsequent operations that need treatments by manager or the auditor.…”
Section: The Theoretical Framework and Previous Studiesmentioning
confidence: 99%
“…However, more recent studies suggest that framing may affect auditor judgment under some circumstances. Chung et al (2013) review research in accounting on the role of biases in auditor judgments and speculate that, in some settings, a positive frame may lead auditors to seek information confirming client assertions and engage in less thorough information processing. At the same time, a negative frame may encourage auditors to avoid seeking information that confirms a client's assertions and to engage in information processing that is more thorough.…”
Section: Effect Of Step Frame On Audit Time Budgeting Judgmentsmentioning
confidence: 99%
“…
A research synthesis team formed by the Auditing Section of the American Accounting Association recently authored a paper (Chung et al 2013) addressing the audit of subsequent events (SEs). The audit of SEs is a difficult audit area, as approximately one-third of the Public Company Accounting Oversight Board's inspection reports and numerous Securities and Exchange Commission enforcement releases identify deficiencies in this area (Chung et al 2013). Chung et al (2013) developed a model and proposed a series of research questions encouraging future academic research in this area.
…”
mentioning
confidence: 99%